HARGA MINYAK INDONESIA PERIODE 1971-2016 - Sultan, Sultan; Sarungu, JJ. (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2018)
Indonesian Oil Prices Period 1971-2016. Oil Price is an important indicator to see the performance of a country's development success. The use of oil as the world's main energy source in general and Indonesia in particular is driven by industrialization. The more industries in a country, the greater the energy sources they need. Novelty This research uses time series data for the period 1971-2016 (46 observations), the analysis of the least squares method equation model (OLS). The purpose of this study was to examine and create empirical evidence of the relationship of world oil prices, economic growth and domestic oil prices in the previous year to domestic oil prices. The method used is descriptive and econometric analysis approach to the least squares equation model. The expected results from this research will provide information on the policy of the transmission mechanism of oil prices in Indonesia. The results showed that the world oil price, economic growth and domestic oil prices in the previous year had a positive effect on domestic oil prices during the study period 1971-2016